2018
DOI: 10.3390/molecules23040788
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Effects of EGCG on Chromosomal Stability and Cell Growth between Normal and Colon Cancer Cells

Abstract: The tea catechin epigallocatechin-3-gallate (EGCG) proved to be the most potent physiologically active tea compound in vitro. It possesses antioxidant as well as pro-oxidant properties. EGCG has the effect of inducing apoptosis of tumor cells and inhibiting cell proliferation. Whether this effect is associated with the antioxidant or pro-oxidative effects of EGCG affecting the genome stability of normal and cancer cells has not been confirmed. Here, we selected Human normal colon epithelial cells NCM460 and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…It is reported to present anti-cancer effects in variety of cancer cells, including lung, colorectal, prostate, stomach, liver, cervical, breast, leukemia, gastric, bladder cancers [85][86][87][88][89][90]. Among its anti-cancer activities, EGCG exhibits multiple pharmacological actions, including the suppression of cell growth, proliferation, metastasis and angiogenesis, induction of apoptosis, and enhancement of anti-cancer immunity [85,86,[91][92][93][94].…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…It is reported to present anti-cancer effects in variety of cancer cells, including lung, colorectal, prostate, stomach, liver, cervical, breast, leukemia, gastric, bladder cancers [85][86][87][88][89][90]. Among its anti-cancer activities, EGCG exhibits multiple pharmacological actions, including the suppression of cell growth, proliferation, metastasis and angiogenesis, induction of apoptosis, and enhancement of anti-cancer immunity [85,86,[91][92][93][94].…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…GTPs exhibit anticancer effects via the regulation of different cancer-related processes and factors, including DNA methylation, histone modification, micro-RNA, and proteins [ 5 , 14 , 15 , 16 , 17 ]. They also play an important role via the regulation of apoptosis, growth, invasion, and angiogenesis in various types of malignancies [ 13 , 15 , 18 , 19 ]. A recent study showed that GTPs can influence the pathological roles of not only cancer cells, but also cancer stem cells [ 17 ].…”
Section: Anticancer Effects Of Green Tea Polyphenolsmentioning
confidence: 99%
“…Various cancer-related molecules have been reported to be modulated by GTPs. In fact, many studies have reported that GTPs inhibited cell growth and induced apoptosis in various types of malignancies [ 19 , 27 , 28 ]. In addition, these polyphenols modulate the functions of various cancer-related signaling molecules.…”
Section: Anticancer Effects Of Green Tea Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…pancreatic and colon cancer (Baek et al, 2004;Lim et al, 2006;Kürbitz et al, 2011;Cordero-Herrera et al, 2013) (Sukhthankar et al, 2010;Kuerbitz et al, 2011;Wang et al, 2011b;Lee et al, 2012;Luo et al, 2014;Fu et al, 2019) attenuating angiogenesis MPI, ACTA1, PECAM1 lung cancer (Deng et al, 2019) inhibiting metastasis CDH1/2, CSRC, ERBB2, ESR2, MAPK8, MIR138, NFKB, PTK2, SLC22A5, SNAIL1/2, TJP1, VIM, lung, colon, breast, bladder, and prostate cancer (Shimizu et al, 2005a;Punathil et al, 2008;Sen et al, 2010;Sen and Chatterjee, 2011;Deng and Lin, 2011;Ko et al, 2013;Mukherjee et al, 2014;Li et al, 2015;Huang et al, 2016b;Luo et al, 2017) promoting apoptosis and autophagy AKT1, AP1, APAF1, ATM, BAD, BAX, BCL2/L1, BIRC5, CASP2/3/8/9, CCNB1, CDC2, CDKN1A, CYC, DIABLO, EGFR, ERBB2/3, FAS, FASLG, GDF15, JNK1/2, KRAS, MAPK1/14, MLH1, MSH2, MTCO2, MYC, NFKB, PARP1, PEG2, PGE2, PIK3CA, PRKAA2, PTEN, PTK2, SP1, TP53 pancreatic, lung, colon, head and neck, breast, and bladder cancer (Shimizu et al, 2005b;Park et al, 2009;Deng and Lin, 2011;Kang et al, 2013;Cerezo-Guisado et al, 2015;Li et al, 2016;Luo et al, 2017;Huang et al, 2017;Ni et al, 2018;Gu et al, 2018;Wei et al, 2018;Lu et al, 2019) sensitizing chemotherapy ABCG2/B1, ATP7A/B, BAX, BBC3, CASP3/7/9, CDKN...…”
Section: Discussionmentioning
confidence: 99%